Global Stability of a Stochastic Lotka-Volterra Cooperative System with Two Feedback Controls (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, a class of Lotka-Volterra cooperation system and corresponding stochastic system with two feedback controls which are affected by all species are considered. We obtain some sufficient criteria for local stability and global asymptotic stability of equilibria of the systems. Our study shows that these equilibria could be globally stable by adjusting coefficients of the feedback control variables and stochastic perturbation parameters. Numerical simulations are presented to demonstrate our main result.
Keywords: Lotka-Volterra cooperative system; Feedback controls; Stochastic perturbation; Global stability.